A Bayesian network to represent a data quality model. (27th December 2007) - Caro, Angelica; Calero, Coral; Sahraoui, Houari A.; Piattini, Mario
Web portals provide data to many people where data consumers need to assess Data Quality (DQ). In our previous work a Portal Data Quality Model (PDQM) was developed. PDQM is focused on data consumers' perspective and is composed by 33 attributes appropriate for DQ evaluation. Now, we have organised these attributes into a generic and operational structure. Considering the uncertainty inherent in perception of quality, we decided to use a probabilistic approach, using Bayesian Networks (BNs). This paper, explains the definition of the BN structure that supports PDQM.